1999
DOI: 10.1038/sj.gt.3301021
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal extension of the MHC class II-associated invariant chain by an antigenic sequence triggers activation of naive T cells

Abstract: In vitro and in vivo activation of T cells was investigated T hybridoma cells. Nonprofessional APC expressing with invariant chain-antigen fusion protein. The CD4 T cell recombinant Ii HEL and H2-A k are also able to activate epitope amino acid 52-61 of hen egg lysozyme (HEL) was naive T cells from 3A9 TCR transgenic mice, a result not attached to the C-terminal end of invariant chain (Ii).achieved with peptide pulsed APC. To elicit an in vivo Expression of this recombinant Ii HEL directs the T cell immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 51 publications
0
18
0
1
Order By: Relevance
“…4,[33][34][35] It is demonstrated that DC expressing Ii-OVA fusion cDNA with the OVA-specific MHC class I and II, or the MHC class II epitope only, were effective in eliciting potent MHC class II-restricted T cell responses in DC/T cell cocultures in vitro. Interestingly, efficient MHC class I presentation was also achieved although the Ii fusion targets the antigen to the MHC class II processing pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[33][34][35] It is demonstrated that DC expressing Ii-OVA fusion cDNA with the OVA-specific MHC class I and II, or the MHC class II epitope only, were effective in eliciting potent MHC class II-restricted T cell responses in DC/T cell cocultures in vitro. Interestingly, efficient MHC class I presentation was also achieved although the Ii fusion targets the antigen to the MHC class II processing pathway.…”
Section: Discussionmentioning
confidence: 99%
“…PCR primers were designed to introduce DraIII restriction sites at either end of the fragments. PCR fragments were inserted into the DraIII site of pEXV3-Ii31 34 and Ii-OVA fusions were then cloned into EcoRI of pcDNA3 thereby generating pcDNA3-Ii-OVA.II and pcDNA3-Ii-OVA.I+II plasmid, respectively. The integrity of the Ii-OVA fusions was confirmed by DNA sequencing.…”
Section: Plasmid Vectorsmentioning
confidence: 99%
“…We therefore sought to identify, among the seven structurally conserved HIV-1 p24-derived CD4 + T cell epitopes, those that would best support the induction of potent cytolytic responses. To compare the Th1 helper potential of these epitopes, they were introduced separately in the C-terminal portion of the mouse invariant chain [18]. Other lysosomal molecules (LAMP, LIMP) have been used as cargo molecules to sort antigens to lysosomal compartments, but with mixed success [19].…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic peptides bind to class II dimers and are presented on the cell surface of APC to CD4 T cells. 15 Co -players of antigen processing are the invariant chain (li ) , MHC encoded DM and DO molecules, and certain proteases. 16 ± 18 The transactivator CIITA (a non ±DNA -binding transactivator, which regulates the expression of MHC class II, HLA -DM, and invariant chain ) behaves as a master controller of constitutive and inducible MHC class II gene activation.…”
mentioning
confidence: 99%